BEAUTY AND WOMEN ON CHANDANA VAHINI - Gowda, Harisha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Kamala Hampana says about beauty, “From the day man and woman were created, their mutual attraction began. As man became known for his masculinity and virility, woman became known for her shyness, tenderness and beauty. A woman was a secret hideout for a man, a dream nest, a challenge for a man who tried to understand her in many ways, a man who recognized the steps of a fish and counted the stars could not understand a woman’s mind. Finally, when he tried to understand her, he opened his mouth to praise a woman’s open spaces with a smile, and he has not closed his mouth till today. He who praises and describes a woman’s organs will probably never give his tongue a break; this statement is also worthy of ridicule.”2 Doordarshan Chandan Channel’s programs are different and diverse from other private Doordarshan Channel’s programs because it is a government-owned autonomous organization.